Penguatan Pendidikan Karakter Melalui Gerakan Seribu Kata dan Kalimat Positif (Serbukatif) Di SDN Pengadilan 3 Kota Bogor - Afifah Adlina Zahra (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2026)
Character education is a crucial aspect in shaping ethical and responsible young generations. This study aims to analyze the implementation of the "Serbukatif" movement (A Thousand Positive Words and Sentences) in strengthening character education at SDN Pengadilan 3 in Bogor City. Using a qualitative approach with a descriptive method, data were collected through observation, interviews, and documentation. Serbukatif is a program that encourages students to write and share positive sentences daily, both verbally and via social media, to foster a culture of respectful communication. The findings indicate that this program significantly contributes to the development of character values such as honesty, responsibility, and empathy, while also improving students' language etiquette. Additionally, it creates a more conducive learning environment and fosters harmonious interpersonal relationships within the school. These results affirm that the Serbukatif movement can serve as an effective strategy for character development from an early age and holds potential as a value-based educational model adaptable to the challenges of the digital era.